Anticancer Effect of Spices Used in Mediterranean Diet: Preventive and Therapeutic Potentials - Talib, Wamidh H.; AlHur, Mallak J.; Al.Naimat, Sumaiah; Ahmad, Rawand E.; Al-Yasari, Arkan Hadi; Al-Dalaeen, Anfal; Thiab, Samar; Mahmod, Asma Ismail (Frontiers in Nutrition, 2022)
Cancer is one of the leading causes of death worldwide, with almost 10 million cancer-related deaths worldwide in 2020, so any investigation to prevent or cure this disease is very important. Spices have been studied widely in several countries to treat different diseases. However, studies that summarize the potential anticancer effect of spices used in Mediterranean diet are very limited. This review highlighted chemo-therapeutic and chemo-preventive effect of ginger, pepper, rosemary, turmeric, black cumin and clove. Moreover, the mechanisms of action for each one of them were figured out such as anti-angiogenesis, antioxidant, altering signaling pathways, induction of cell apoptosis, and cell cycle arrest, for several types of cancer. The most widely used spice in Mediterranean diet is black pepper (Piper nigrum L). Ginger and black cumin have the highest anticancer activity by targeting multiple cancer hallmarks. Apoptosis induction is the most common pathway activated by different spices in Mediterranean diet to inhibit cancer. Studies discussed in this review may help researchers to design and test new anticancer diets enriched with selected spices that have high activities.